Teachers’ Strategies To Motivate Students In Learning English At A Vocational High School In Rimbo Bujang - Nita Prastuti (Cahaya Ilmu Cendekia Publisher, 2020)
Purpose of the study: The purpose of this research were to investigate, to report and to discuss about teachers’ strategies and how the teachers apply the strategies to motivate students in teaching and learning English at a vocational high school. Methodology: Data in this thesis were collected through interview with English teachers and observation in the classrooms. Data from interview section were analyzed by transcribing the data, becoming familiar with the data, coding, theming and reporting. Main Findings: There were four major themes about strategies to motivate vocational students in learning English in this case study which included create relax atmosphere in the class, having awareness to the students’ characteristics, connecting the teaching process to the real life and more creative in the teaching process. The significant of this research are as a source of information for teachers and teacher to be about strategies to motivate vocational students in learning English. Novelty/Originality of this study: The novelty in this research is the strategy for student motivation in learning is carried out at Rimbo Bujang